2010
DOI: 10.1002/zoo.20358
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐recognition training: a conservation strategy to increase postrelease survival of hellbenders in head‐starting programs

Abstract: For species with declining populations, captive rearing with subsequent release into natural habitats ("head-starting") is often used as part of a conservation strategy. One challenge to head-starting programs is that head-started individuals can suffer high rates of postrelease predation. Head-starting programs are currently being established for hellbenders (Cryptobrancus alleganeinsis), large aquatic salamanders that are experiencing population declines throughout much of the species' range. Although hellbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 49 publications
1
35
2
Order By: Relevance
“…These results substantiate other work that found that amphibians, including hellbenders, have innate behavioral responses to predator kairomones [32,59,60]. Crane and Mathis [11] found that larval hellbenders, 21-25 weeks old, increase their swimming when exposed to trout kairomones, which they interpreted as evidence of escape behavior. Our findings differ from Crane and Mathis [11], likely because we presented live amphibian prey to largemouth bass as food.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results substantiate other work that found that amphibians, including hellbenders, have innate behavioral responses to predator kairomones [32,59,60]. Crane and Mathis [11] found that larval hellbenders, 21-25 weeks old, increase their swimming when exposed to trout kairomones, which they interpreted as evidence of escape behavior. Our findings differ from Crane and Mathis [11], likely because we presented live amphibian prey to largemouth bass as food.…”
Section: Discussionsupporting
confidence: 89%
“…Crane and Mathis [11] found that larval hellbenders, 21-25 weeks old, increase their swimming when exposed to trout kairomones, which they interpreted as evidence of escape behavior. Our findings differ from Crane and Mathis [11], likely because we presented live amphibian prey to largemouth bass as food. Although their study elicited responses using hellbender slime as an alarm cue, they fed their fish a diet of floating trout feed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations